2005
DOI: 10.1016/j.jspi.2003.08.020
|View full text |Cite
|
Sign up to set email alerts
|

An asymptotic approach to progressive censoring

Abstract: Progressive Type-II censoring was introduced by Cohen (1963) and has since been the topic of much research. The question stands whether it is sensible to use this sampling plan by design, instead of regular Type-II right censoring. We introduce an asymptotic progressive censoring model, and find optimal censoring schemes for location-scale families. Our optimality criterion is the determinant of the 2 × 2 covariance matrix of the asymptotic best linear unbiased estimators. We present an explicit expression for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…[S2] Fix (n 1 , n 2 ) = (5, 15), (10,10) and (15,5) for N = 20; (n 1 , n 2 ) = (5, 35), (10, 30), (15,25) and (20, 20) for N = 40; and search for the optimal allocation with effective sample sizes (m 1 , m 2 ) and censoring locations for different optimality criteria subject to the constraint…”
Section: -Stress-level Casementioning
confidence: 99%
See 1 more Smart Citation
“…[S2] Fix (n 1 , n 2 ) = (5, 15), (10,10) and (15,5) for N = 20; (n 1 , n 2 ) = (5, 35), (10, 30), (15,25) and (20, 20) for N = 40; and search for the optimal allocation with effective sample sizes (m 1 , m 2 ) and censoring locations for different optimality criteria subject to the constraint…”
Section: -Stress-level Casementioning
confidence: 99%
“…[S2] Fix (n 1 , n 2 , n 3 , n 4 ) = (0, 10, 10, 0), (3,7,7,3), (5,5,5,5), (6,4,4,6) and (10, 0, 0, 10) for N = 20; (n 1 , n 2 , n 3 , n 4 ) = (0, 20, 20, 0), (5,15,15,5), (8,12,12,8), (10, 10, 10, 10), (15,5,5,15) and ( …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Progressive type II censoring, first proposed by [6], is one of the most common censoring systems in lifetime scenarios and has received significant attention in the literature. The authors of [7] showed, for example, that in many instances, type II progressive-censoring schemes, which include ordinary type II one-stage right censoring as a particular case, could greatly outperform standard type II censoring. Reference [8] provides a brief overview of the progressive type II censoring technique.…”
Section: Introductionmentioning
confidence: 99%
“…Hofmann et al (2005), introduced an asymptotic progressive censoring model, and found optimal censoring schemes for location-scale families based on the determinant of the covariance matrix of the asymptotic best linear unbiased estimators. The procedure is illustrated numerically when the parent distributions are Weibull and normal.…”
Section: Introductionmentioning
confidence: 99%